Moderasi Beragama Dalam Meningkatkan Nilai-Nilai Ekonomi Islam Melalui Kearifan Lokal Berbasis Filantophy Sosial Masyarakat - Latifah, Eny (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
This research aims to determine Religious Moderation in improving Islamic Economic values ​​through local wisdom based on community social philanthropy on Wages for Malaysian Workers in Karangtawar Village, Laren District, Lamongan Regency. This research method is qualitative with a case study type with data triangulation analysis techniques including documents, interviews and observations to obtain the required data. The results of the research are that existing Islamic economic values ​​include: The basic value of ownership includes the awareness that assets obtained from the wages of migrant workers have rights for other people (the poor). Second, the basic value of justice includes being fair and wise in managing wages resulting from work to equalize people's income by giving alms and donations to those in need. Third, the basic value of balance includes: Equal distribution of income from migrant workers' wages to be given to less fortunate relatives so that it can be used as a source of funding Work. Fourth, the basic value of freedom includes: Malaysian migrant workers are free to provide whatever wages and forms to give to people who cannot afford it. And fifth, the value of togetherness includes the human spirit and brotherhood between those who have excess wealth and those who cannot afford it, which can create unity and togetherness without looking at the differences and diversity that exist in Karangtawar Village, Lamongan Regency.